FENOMENOLOGI ANTUSIASME MASYARAKAT TERHADAP OLAHRAGA BOLA VOLI DI KECAMATAN JUJUHAN - Widya (Master of Physical Culture and Recreation in Nusantara, 2025)
This research is grounded in a new perspective that views sports as part of the social structure that is alive and meaningful for the local community. The type of research employed in this study is qualitative research using a phenomenological approach. The data collected in this study are qualitative in nature, consisting of narratives, opinions, perspectives, and the subjective experiences of the community related to the phenomenon of enthusiasm for volleyball and volleyball tournaments in Jujuhan District. Based on the findings of the study regarding the phenomenon of community enthusiasm for volleyball and the organization of volleyball tournaments in Jujuhan District, it can be concluded that the high level of community participation and support does not occur by chance but is the result of a combination of social, cultural, and emotional factors. Volleyball tournaments, particularly annual events such as the Tanikek Cup, have become a recreational space that simultaneously strengthens social cohesion among residents.